Effect of Dried Brewers’ Grains as a Source of Fibre in the Diet of Angora Rabbits on the Growth Performance - Siddaramanna; Reddy, B.S.V.; Madhusudhan, H.S.; Prabhu, B.H. Manjunatha; Mohan, K.; Jayashankar, M.R. (Pakistan Journal of Nutrition, 2009)
An attempt was made to study the effect of incorporation of Dried Brewers’ Grains (DBG) as a source of fibre on the growth performance of Angora rabbit. Forty Angora rabbits of eight month age were selected, sheared and grouped into four body weight categories namely Low Weight (LW), Medium Low Weight (MLW), Medium Heavy Weight (MHW) and Heavy Weight (HW) groups, each with 10 rabbits. There were five treatments, namely, T1 (Control with 40% Dehydrated Lucerne Meal (DLM) as a major fibre source), T2 (Equal parts of DLM and DBG as major fibre sources), T3 (40% DBG as a major fibre source without DLM), T4 (Ricebran extraction as a major fibre source without DLM), T5 (DLM and sunflower cake as major fibre source). Two rabbits from each body weight category were randomly allotted to all the treatments (8 rabbits in all) such that average initial weight was uniform under all dietary treatments. All rabbits were fed ad libitum and weighed once a week. The rabbits had an average body weight of 2.83, 2.97, 2.97 and 3.05 kg with mean gain in body weight as 12.7, 13.3, 8.8 and 9.8 g per day showed the feed efficiency of 11.8, 12.2, 20.8 and 15.3 under LW, MLW, HW and MHW groups respectively, among which feed efficiency of first three were statistically similar (p = 0.01) within themselves whereas, LW and MLW category were significantly different (p = 0.01) from HW category. Despite a non-significant (p = 0.01) effect in the gain in body weight or feed efficiency due to treatments, the T2 diet (13.8) may prove satisfactory.